2006
DOI: 10.1111/j.1468-1331.2006.01493.x
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines on routine cerebrospinal fluid analysis. Report from an EFNS task force

Abstract: A great variety of neurological diseases require investigation of cerebrospinal fluid (CSF) to prove the diagnosis or to rule out relevant differential diagnoses. The objectives were to evaluate the theoretical background and provide guidelines for clinical use in routine CSF analysis including total protein, albumin, immunoglobulins, glucose, lactate, cell count, cytological staining, and investigation of infectious CSF. The methods included a Systematic Medline search for the above-mentioned variables and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
244
0
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 279 publications
(272 citation statements)
references
References 66 publications
(74 reference statements)
4
244
0
5
Order By: Relevance
“…Delayed treatment of false negative cases may be fatal. However, high specificity is desired to exclude expensive treatment of false positive cases (8). Previous studies have shown CSF lactate to have the highest sensitivity (89%-100%) and specificity (96%-100%) for discriminating acute untreated bacterial meningitis from viral meningitis, when the threshold limit was set at 3.5 mmol/L (36,37).…”
Section: Figure 1 Csf Lactic Acid (Mmol/l) Concentration In the Studimentioning
confidence: 99%
See 1 more Smart Citation
“…Delayed treatment of false negative cases may be fatal. However, high specificity is desired to exclude expensive treatment of false positive cases (8). Previous studies have shown CSF lactate to have the highest sensitivity (89%-100%) and specificity (96%-100%) for discriminating acute untreated bacterial meningitis from viral meningitis, when the threshold limit was set at 3.5 mmol/L (36,37).…”
Section: Figure 1 Csf Lactic Acid (Mmol/l) Concentration In the Studimentioning
confidence: 99%
“…CSF lactic acid (LA) is considered a good biomarker for differentiating bacterial from viral meningitis at a cut-off of 3.5 mmol/L (8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…The detection of intrathecal synthesis of oligoclonal IgG with IEF is a useful diagnostic tool both in MS and other disorders of the CNS (Deisenhammer 2006). IEF with immunoblot was used to examine the clonal patterns of intrathecally synthesised IgG and of virus-specific…”
Section: Qualitative Analysis Of Igg and Igg Antibodiesmentioning
confidence: 99%
“…Laboratory examination of cerebrospinal fluid is irreplaceable for diagnosing a wide spectrum of neurological diseases (Deisenhammer et al., 2006). Cytological examination is considered one of the substantial methods of CSF diagnostics (Sobek et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Tumorous impairment of CNS is the highest priority for the application of CSF cytology (Deisenhammer et al., 2006; Sobek et al., 2012). It is a minimally invasive diagnostic method, yet capable enough to ensure crucial information concerning not only the mere presence of tumorous cells in CSF but also their closer identification which is fundamental for consecutive therapy and for the patient's prognosis.…”
Section: Introductionmentioning
confidence: 99%